Learning From Experience: Improving Early Tracheal Extubation Success After Congenital Cardiac Surgery*. Issue 7 (July 2016) - Winch, Peter D.; Staudt, Anna M.; Sebastian, Roby; Corridore, Marco; Tumin, Dmitry; Simsic, Janet; Galantowicz, Mark; Naguib, Aymen; Tobias, Joseph D.
Abstract : Objectives: The many advantages of early tracheal extubation following congenital cardiac surgery in young infants and children are now widely recognized. Benefits include avoiding the morbidity associated with prolonged intubation and the consequences of sedation and positive pressure ventilation in the setting of altered cardiopulmonary physiology. Our practice of tracheal extubation of young infants in the operating room following cardiac surgery has evolved and new challenges in the arena of postoperative sedation and pain management have appeared. Design: Review our institutional outcomes associated with early tracheal extubation following congenital cardiac surgery. Patients: Inclusion criteria included all children less than 1 year old who underwent congenital cardiac surgery between October 1, 2010, and October 24, 2013. Measurements and Main Results: A total of 416 patients less than 1 year old were included. Of the 416 patients, 234 underwent tracheal extubation in the operating room (56%) with 25 requiring reintubation (10.7%), either immediately or following admission to the cardiothoracic ICU. Of the 25 patients extubated in the operating room who required reintubation, 22 failed within 24 hours of cardiothoracic ICU admission; 10 failures were directly related to narcotic doses that resulted in respiratory depression. Conclusions: As a result of this review, we have instituted changes in our cardiothoracic ICU postoperative care plans. We have developed a neonatal delirium score, and have adopted the "Kangaroo Care" approach that was first popularized in neonatal ICUs. This provision allows for the early parental holding of infants following admission to the cardiothoracic ICU and allows for appropriately selected parents to sleep in the same beds alongside their postoperative children.